Implementation of Whole-School Approaches to Physical Activity: Results and Usability of a Rapid Review (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The WHO recommends 60 minutes of daily moderate-vigorous physical activity (PA) for children. The school is an important setting for physical activity promotion and whole-school approaches to physical activity (WSA-PA) have been recommended as best practice in schools. Despite this, the uptake is low, and challenges relate to implementation and sustainability. A new national Danish partnership to promote implementation of WSA-PA at scale was launched in January 2025. The partnership aims to develop, implement, and evaluate an evidence-informed WSA-PA focused on a long-term commitment and close collaboration between two research institutions and important stakeholders, including The Association of Danish Pupils and Association of School Leaders. This study will present findings from a rapid review on facilitators and barriers for implementation, and implementation strategies of WSA-PAs in primary and secondary schools.Methods: The study work-group will develop specific research questions and define criteria and boundaries for the review, to ensure relevance for the partnership aim. A rapid yet systematic approach inspired by PRISMA guidelines will be conducted in spring 2025. The databases MEDLINE, ERIC, and Web of Science will be searched to identify intervention studies utilising WSA-PA in school settings. Data extraction and analysis will be inspired by the Consolidated Framework for Implementation Research. The results will be presented and discussed through co-creational workshops in the partnership to inform the development of the Danish WSA-PA.Results: The review will ensure timely and evidence-informed recommendations for the partnership. The protocol and findings will be presented at the conference, providing a comprehensive overview of the review outcomes and further elucidating their implications for development and implementation of the Danish WSA-PA.Conclusion: This study highlights the benefits of applying a rapid systematic review as an academic tool to provide timely input in research-practice partnerships, thus enabling their foundation on the best available evidence. The findings will provide new knowledge on implementation strategies, barriers, and facilitators for implementation of WSA-PA and serve as an inspiration for other countries, researchers, or organisations seeking to increase PA through WSA-PA.Support/Funding Source: The project is funded by Centre for Childhood Health.